2006
DOI: 10.1099/jmm.0.46383-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Phe206Leu polymorphism of L-selectin and brucellosis

Abstract: Brucellosis remains a major zoonosis worldwide; therefore, better understanding of its immunology is a priority for the development of new therapeutic and vaccination strategies. Genetic factors appear to have an important role in the pathogenesis of infectious diseases such as brucellosis. Adhesion molecules, such as members of the selectin family, participate in the interaction between leukocytes and the endothelium, as well as in inflammatory cell recruitment. The impact of L-selectin polymorphisms on bruce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
(21 reference statements)
3
17
1
Order By: Relevance
“…Because L‐selectin also has a role in attracting leukocytes to inflammatory sites (28), we analyzed the L‐selectin Phe206Leu polymorphism in patients with periodontitis. Although recent studies have addressed the significant association between the Phe206Leu polymorphism of L‐selectin with certain disorders such as immunoglobulin A nephropathy (29) and brucellosis (22), we were not able to detect any statistically significant association of this polymorphism with periodontitis. This finding indicates that different genes appear to be related to host susceptibility for periodontitis.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Because L‐selectin also has a role in attracting leukocytes to inflammatory sites (28), we analyzed the L‐selectin Phe206Leu polymorphism in patients with periodontitis. Although recent studies have addressed the significant association between the Phe206Leu polymorphism of L‐selectin with certain disorders such as immunoglobulin A nephropathy (29) and brucellosis (22), we were not able to detect any statistically significant association of this polymorphism with periodontitis. This finding indicates that different genes appear to be related to host susceptibility for periodontitis.…”
Section: Discussioncontrasting
confidence: 77%
“…The polymorphisms investigated in the present study have been previously associated with diseases/conditions such as coronary artery disease (16,17), atherosclerosis (18,19), high blood pressure (20), systemic lupus erythromatosus (21) and brucellosis (22). As no study has yet been undertaken on the possible association between the E‐selectin Ser128Arg (A561C) and L‐selectin Phe206Leu (T668C) polymorphisms and periodontal disease, we evaluated their contribution in the susceptibility to periodontitis.…”
mentioning
confidence: 99%
“…However, the roles of these two variables in asthma have not been determined. In addition, our previous studies in an Iranian population indicated that there is an association between inflammatory diseases (coronary artery diseases and brucellosis) and F206L polymorphism of l ‐selectin . The present study was conducted to determine the association of plasma levels of s l ‐selectin and F206L polymorphism of l ‐selectin with asthma in a population from Hamadan province of Iran.…”
Section: Introductionmentioning
confidence: 89%
“…In Chinese patients with coronary heart disease, the frequency of the L-selectin gene 213P allele was significantly higher than that in the control group [60]. The allelic frequency of 206L allele was also found significantly increased among Iranian patients with brucellosis than in healthy individuals [41]. Among Asian Indian pediatric patients with celiac disease [39], the allelic frequency of L-selectin 206 L was found at an increased frequency, although insignificant, in celiac disease patients as compared with healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…A polymorphism in the gene encoding L-selectin has been identified in exon 3, which encodes for the epidermal growth factor (EGF) domain. A phenylalanine to leucine mutation at position 206 and its association with celiac disease [39], coronary heart disease [40], and brucellosis [41] has been reported.…”
Section: Introductionmentioning
confidence: 98%